Importance of Oxidative Stress and Antioxidant System in Health and Disease - Sabuncuoğlu, Suna; Yalcinkaya, Ahmet (Biochemistry, 2023)
Oxidative stress is a major contributor to the etiology of chronic disorders like cancer, diabetes, neurodegenerative diseases, and cardiovascular diseases. Long-term exposure to elevated levels of pro-oxidant substances can lead to structural damage in mitochondrial DNA as well as functional changes in a number of enzymes and cellular components, which can lead to abnormalities in gene expression. Modern lifestyles, which include eating processed food, exposure to a variety of chemicals, and not exercising, are significant factors in the development of oxidative stress. However, the ability of medicinal plants with antioxidant capabilities to cure or prevent a number of human illnesses in which oxidative stress appears to be a contributing factor has been demonstrated. A growing body of research links free radicals to the etiology of many diseases, supporting the use of antioxidants as a promising therapeutic strategy for the management of pathologies caused by free radicals. Despite these remarkable advances, there is still much to learn about the relationship between free radicals and antioxidants. Understanding the principles behind pathological and physiological disorders caused by free radicals is crucial. Importance of Oxidative Stress and Antioxidant System in Health and Disease contributes to understanding the fundamental principles of oxidative stress and the effects of antioxidants on disease and health.